Regional disparities in health literacy for chronic diseases: focusing on healthcare resources and local extinction index - Seokmin Ji; Seokmin Ji; Young Gyu Kwon; Young Gyu Kwon; Hyunseo Lee; Hyunseo Lee; Chaehwan Shin; Chaehwan Shin; Minsung Sohn; Mankyu Choi; Mankyu Choi (Frontiers Media S.A., 2024)
ObjectiveThis study compared disparities between community health characteristics and health literacy levels for hypertension and diabetes by combining community-level characteristics, such as the local extinction index and healthcare resources, with individual-level characteristics based on the Andersen healthcare utilization model.MethodData obtained from the 2017, 2019, and 2021 Community Health Surveys, Korean Statistical Information Service, and National Health Insurance Service were analyzed. The analyses included spatial analysis, propensity score matching, and cross-analysis.ResultsTwenty-five extinction-risk regions (ERRs) were identified in 2017, 26 in 2019, and 29 in 2021, indicating a high risk of extinction and insufficient healthcare resources in non-metropolitan regions. Based on analyses of demographic changes and unmet medical needs at the individual level, we observed increased age and economic activity, decreased healthcare access, and lower education levels in ERRs compared to non-extinction-risk regions (NERRs). No significant differences were found between the regions regarding diagnosis or medication use concerning the health literacy gap for hypertension and diabetes. However, individuals in ERRs were significantly less likely than those in NERRs to be aware of such diseases or educated about their management.DiscussionGiven that healthcare services in ERRs focus on chronic disease management rather than prevention, we propose two directions to reduce health disparities in ERRs. First, the government should encourage cooperation with private healthcare organizations to ensure the provision of health education programs in vulnerable areas. Second, improvements in awareness and education regarding chronic disease management can be achieved through digital healthcare and telemedicine. This study identifies regional disparities in chronic disease prevention and management, providing a basis for policies to ensure healthier communities with health equity.